Analiza Pewnej Klasy Płaskich Dwuwarstwowych Kratownic - Obrębski, J.B. (Engineering Transactions, 1972)
In the paper presented is the static analysis of plane, double-Iayer trusses with a horizontal projection revealing a hexagonal pattern; the analysis is aimed at numerical calculations. The nodes of the truss are subject to arbitrarily directed concentrated forces. The formulae derived in the paper may serve as a basis for the solution of arbitrarily loaded and supported structures of the type described. Given are numerical examples.